SAÚDE E AMBIENTE NO CENÁRIO DE IMPLANTAÇÃO DA REFINARIA PREMIUM I EM BACABEIRA - MA - Castro, Natercia Gomes de (2013)
The literature points to the importance of health and environment as close as a concept and practice. The result of this approach to health care would be to value the environment as a determinant of health problems, as an ecologically balanced environment is more propellant health and quality of life. This research aimed to evaluate the economic and social context of health conditions and environment in the municipality of Bacabeira. The study is characterized as qualiquantitativo-descriptive research was the site of the city of Bacabeira-MA, representation sample was 308 participants. For data collection, interviews were conducted with semi-structured questionnaires. The data were organized in a database program Excel 2007 and held the tab. The research results demonstrate a low socioeconomic level of education, high unemployment, household income of the vast majority does not exceed a minimum wage and benefit program Bolsa Família is the main source of income of these people showing a marked socioeconomic vulnerability of the population. The sanitation situation is an almost total absence of a proper system, with no sewage disposal system, a deficit in water supply and garbage collection. We observed a more precarious in rural compromising the quality of life. With respect to population health is extremely dissatisfied with the services, because besides the lack of structure of health facilities and lack of hospital supplies including medicines adds up to a lack of resolution of problems of the community. The waterborne diseases were the most predominantly observed the worms and dengue showing the intrinsic relationship to the bad sanitation conditions of the town and the lack of health-related projects. The environmental awareness of the population regarding the project showed us a superficial knowledge on environmental issues and highlighted the great expectation of the population with regard to job creation and improving the quality of life of residents. Therefore, it is necessary to articulate public policies on housing, health, environment and urban infrastructure for the city of Bacabeira, including policies conducive to sustainable economic growth as a more equitable distribution of resources, linked to interventions that improve essential conditions of the population, such as access to health services, healthy environments (dwellings safe, sanitary and decent), particularly better access to water and sanitation, nutrition and educational opportunities.